TINJAUAN YURIDIS TENTANG KAWIN/PERNIKAHAN SECARA KONTRAK MENURUT IMPLEMENTASI PASAL 1320 DAN 1243 KITAB UNDANG-UNDANG HUKUM PERDATA (KUHPER) - Aris Setyanto Pramono; Safiulloh Safiulloh (LPPM Universitas Bina Bangsa, 2022)
This study aims to determine whether or not a dispute over default can be resolved in a marriage or marriage that is carried out by contract. Because in the rules of the marriage law No.1 of 1974 there is no state that marriage is carried out with a certain time limit and the parties have certain purposes and clauses, and in religion as a marriage is carried out because on the basis of mutual love without any coercion and solely aims only to worship Allah Almighty / God Almighty. In one of the valid conditions in the contract or agreement in article 1320 of the Criminal Code is